2007
DOI: 10.1159/000110546
|View full text |Cite
|
Sign up to set email alerts
|

5-Fluorouracil, Leucovorin and Oxaliplatin plus Bevacizumab in the First-Line Treatment of Metastatic Colorectal Cancer: A Single-Institute Study

Abstract: Background: The addition of bevacizumab to 5-fluorouracil, leucovorin and oxaliplatin (FOLFOX) improved the time-to-progression (TTP) and overall survival (OS) in comparison to FOLFOX in the second-line treatment of metastatic colorectal cancer (MCRC). However, limited survival data are available to support FOLFOX plus bevacizumab in a first-line setting. We conducted a retrospective study of first-line FOLFOX plus bevacizumab to better characterize the safety and efficacy of this regimen in the first-line tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
22
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…The safety and efficacy of bevacizumab, the monoclonal antibody that targets vascular endothelial growth factor (VEGF; ref. 7), in combination with FOLFIRI or FOLFOX, was also evaluated recently (8,9). Although both studies were carried out with small Cancer Therapy: Preclinical…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The safety and efficacy of bevacizumab, the monoclonal antibody that targets vascular endothelial growth factor (VEGF; ref. 7), in combination with FOLFIRI or FOLFOX, was also evaluated recently (8,9). Although both studies were carried out with small Cancer Therapy: Preclinical…”
mentioning
confidence: 99%
“…The safety and efficacy of bevacizumab, the monoclonal antibody that targets vascular endothelial growth factor (VEGF; ref. 7), in combination with FOLFIRI or FOLFOX, was also evaluated recently (8,9). Although both studies were carried out with small patient numbers, Kang et al concluded that the combination treatment had modest activity and was relatively tolerable in metastatic colorectal cancer that had failed FOLFIRI or FOLFOX.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…More recent studies combining FOLFOX or XELOX with bevacizumab report a grade 3 neuropathy rate of 7–10%, likely reflecting earlier discontinuation of oxaliplatin [13,14]. In this journal, we have also previously reported on our experience with first-line FOLFOX plus bevacizumab chemotherapy [16]. Sixteen percent of patients treated with this combination experienced grade 3 neuropathy and 49% discontinued oxaliplatin prior to progression due to neuropathy [16].…”
Section: Introductionmentioning
confidence: 94%
“…In this journal, we have also previously reported on our experience with first-line FOLFOX plus bevacizumab chemotherapy [16]. Sixteen percent of patients treated with this combination experienced grade 3 neuropathy and 49% discontinued oxaliplatin prior to progression due to neuropathy [16]. The high rate of limiting neuropathy associated with FOLFOX (or XELOX) chemotherapy has triggered the investigation of stop and go FOLFOX regimens where oxaliplatin is electively withdrawn after 3 months from initiation of treatment.…”
Section: Introductionmentioning
confidence: 99%